2010
DOI: 10.1007/s11605-010-1194-y
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Pouch Prolapse: Prevalence, Management, and Outcomes

Abstract: Pouch prolapse is rare, and there are no obvious predisposing factors. Mucosal prolapse may be treated by stool bulking or a local perineal procedure. Full thickness prolapse requires definitive surgery and is associated with risk of pouch loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 9 publications
2
47
0
Order By: Relevance
“…As reported from Joyce et al [3] it is also our experience that the suture rectopexy has higher recurrence rates, and that the complication-and recurrence rates with biological meshes are low. The biological meshes are immunological intent and can be left in place in case of infection.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…As reported from Joyce et al [3] it is also our experience that the suture rectopexy has higher recurrence rates, and that the complication-and recurrence rates with biological meshes are low. The biological meshes are immunological intent and can be left in place in case of infection.…”
Section: Discussionsupporting
confidence: 69%
“…Due to the high recurrence rate, the seventh patient underwent transabdominal pouchopexy with a biological mesh. At nine months follow-up there was no recurrence [3].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It can be either a mucosal or full prolapse, and is observed in approximately 0.3% of patients. 50 Conservative measures include stool-bulking agents and biofeedback, whereas transanal excision of the prolapsed mucosa is a viable choice. 50 Full-thickness pouch prolapse needs abdominal salvage with pouchopexy.…”
Section: Structural and Mechanical Complicationsmentioning
confidence: 99%
“…One study reported 83 patients with pouch prolapse when a survey of colorectal surgeons in North America was conducted, whereas an article from Cleveland clinic identified a rate of 0.3%, 11 patients of 3176. 43,44 In the Cleveland clinic study, both full thickness and mucosal prolapse are seen, and diagnosis were made on physical examiantion alone while 1 patient needed pouchoscopy. 44 Because pouch prolapse is such rare event, recommendations for treatment are based on case reports and case series only.…”
Section: Rare Complications Prolpasementioning
confidence: 99%